Seed germination and seedling growth of beet cultivars subjected to saline stress (Research, Society and Development, 2022)
The objective was to evaluate beet cultivars subjected to salinity during the germination and seedling emergence phase. A completely randomized design was used, arranged in a 3x5 factorial scheme, with four replications. The treatments consisted of three beetroot cultivars (Betty RZ F1, Bettollo and Scarlet Super F1) and five irrigation water salinity concentrations of 0, 50, 100, 150 and 200 mM corresponding to Electrical Conductivities of 0, 6.00, 10 .25, 12.44 and 14.40 dS/m. The percentages of germination and emergence, the germination and emergence speed index (IVG and IVE), mean germination and emergence time (TMG and TME) of the seedlings were calculated. The cultivar Bettollo obtained the best average germination and emergence percentage in the EC of 6.00 dS/m, as well as Scarlet Super at the concentration of 10.25 dS/m, suggesting that these cultivars are more tolerant to these concentrations. Cultivar Betty showed lower germination and emergence at all concentrations. Bettoloo and Scarlet Super suffered decreases both in germination percentage and in emergence in saline concentrations from 10.25 dS/m. The highest EC of water promoted a reduction in the percentage of Germination and IVG, generating an extension of the TMG for all cultivars. The high saline concentrations make it difficult for water to enter the seed, consequently causing a reduction in seedling height, and in the radicle and hypocotyl length of all evaluated cultivars.